Rethinking Mu’âsyarah bil Ma’ruf: A Maqâshid Syari’ah Cum-Mubâdalah Approach - Safdhinar Muhammad An Noor; Arisy Abror Dzukroni; Nasrullah Nasrullah; Moh. Faza Rosyada (JURNAL AT-TURAS, 2024)
This article contends that the principle of mu'âsyaroh bil ma'rûf has been inadequately interpreted, primarily due to its frequent application solely to men, resulting in the neglect and discrimination against women in conceptual formulation and validation. By positioning both men and women as equal participants in defining maqâshid al-syarî'ah, a fairer understanding of mu'asyaraoh bil ma'ruf can be achieved. This qualitative research seeks to redefine the interpretation of mu'âsyarah bil ma'rûf in the Qur'an through the Maqâshid Syarî'ah cum-Mubâdalah approach, integrating the critical concept of mashâlih al-'ibâd in kulliyât al-khams and the Mubâdalah perspective. The Maqâshid al-Syarî'ah cum-Mubâdalah methodology entails merging Maqâshid al-Syarî'ah theory with a perspective emphasizing mutual respect between genders. This study adopts a library research methodology. The findings reveal that, through the Maqâshid al-Syarî'ah cum-Mubâdalah approach, it can be inferred that: 1) mu'asyarah bil ma'ruf extends beyond marital relations to encompass interactions that uphold human values for all individuals; 2) apart from hifdz al-nafs (preservation of life), mu'asyarah bil ma'ruf also encompasses other elements including hifdz al-din (preservation of religion), hifdz al-mal (preservation of wealth), hifdz al-'aql (preservation of intellect), and hifdz al-nasl (preservation of lineage); 3) adherence to the five elements of maqashid sharia is obligatory for both parties engaging in interactions, rather than being imposed solely on one party.